Adaptive Silviculture for Climate Change: From Concepts to Reality Report on a symposium held at Carrefour Forêts 2019 - Nelson Thiffault; Patricia Raymond; Jean-Martin Lussier; Isabelle Aubin; Samuel Royer-Tardif; Anthony W. D’Amato; Frédérik Doyon; Benoit Lafleur; Martin Perron; Jean Bousquet; Nathalie Isabel; Sylvie Carles; et al. (The Forestry Chronicle)
As part of the Carrefour Forêts 2019 Conference, the forest research branch of Quebec’s Ministère des Forêts, de la Faune et des Parcs and the Canadian Wood Fibre Centre of Natural Resources Canada organized jointly the symposium “Adaptive silviculture to climate change: from concepts to reality”. The symposium brought together a hundred actors from the forest sector including engineers, biologists, technicians, private woodlot owners, professors, researchers and students. Speakers from different regions of Quebec and Vermont shared current knowledge related to adaptive silviculture in order to nurture reflexion and dialogue about actions that can be taken today to help forests to adapt with the anticipated changes. The symposium covered the theoretical framework of adaptive silviculture, then offered case studies of different ecosystems, innovative tools or research initiatives. The symposium also included presentations by practitioners who described the challenges and opportunities offered by adaptive silviculture in their professional practice. Based on an interactive discussion, participants identified increased drought events, partial cuttings and mixed-species plantations as important topics on which researchers and practitioners should interact in years to come.